Moving beyond the challenges of learning through technologies: The current status of ICT integration in South African schools - Mnisi, Barutoa Ruth; Mtshali, Thokozani Isaac; Moses, Makgato (Journal of Education and e-Learning Research, 2024)
The purpose of this study was to understand the current status of ICT integration in South African schools. Yet, this study focused on the Tshwane West District schools in Gauteng Province, South Africa. This study employed a descriptive research design to understand the aforesaid phenomenon. Data was collected through interviews and open-ended questionnaires with 10 teachers and one curriculum specialist. This study employed thematic analysis as a qualitative research method. Furthermore, Roger's Diffusion of Innovations is used as a framework. Despite the existence of policies, this study revealed that the integration of ICT remained a significant challenge for several instructors in South Africa. The most interesting part was that schools had improved on most ICT tools to enable access to learning with technologies, but to a greater extent, insufficient internet coverage in classrooms made it impossible for most teachers to appreciate the benefits that come with using tools such as laptops, whiteboards, and online videos. This research proposes the installation of pocket Wi-Fi devices in every classroom in schools to provide comprehensive internet access. This will facilitate interaction between instructors and students through up-to-date learning management systems subscribed to by schools, as well as films. This will promote a digitally viable learning environment that promotes creative opportunities for learners.